2017
DOI: 10.7554/elife.22564
|View full text |Cite
|
Sign up to set email alerts
|

Transient acidosis while retrieving a fear-related memory enhances its lability

Abstract: Attenuating the strength of fearful memories could benefit people disabled by memories of past trauma. Pavlovian conditioning experiments indicate that a retrieval cue can return a conditioned aversive memory to a labile state. However, means to enhance retrieval and render a memory more labile are unknown. We hypothesized that augmenting synaptic signaling during retrieval would increase memory lability. To enhance synaptic transmission, mice inhaled CO2 to induce an acidosis and activate acid sensing ion cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(73 citation statements)
references
References 57 publications
2
71
0
Order By: Relevance
“…If CO2 reactivity is reflective of individual differences in susceptibility to respond to extinction treatment, it could also indicate a differential engagement of networks during extinction, which may make a candidate better suitable for an approach other than extinction (such as reconsolidation blockade or updating). Indeed, this idea would also be very much in line with a recent article showing that inhaling CO2 enhances the ability of retrieval to render an aversive memory labile (Du et al 2017). These findings appear in support of a reconsolidation-based hypothesis.…”
Section: Discussionsupporting
confidence: 62%
“…If CO2 reactivity is reflective of individual differences in susceptibility to respond to extinction treatment, it could also indicate a differential engagement of networks during extinction, which may make a candidate better suitable for an approach other than extinction (such as reconsolidation blockade or updating). Indeed, this idea would also be very much in line with a recent article showing that inhaling CO2 enhances the ability of retrieval to render an aversive memory labile (Du et al 2017). These findings appear in support of a reconsolidation-based hypothesis.…”
Section: Discussionsupporting
confidence: 62%
“…5,7,[13][14][15] Effects of ASIC1A disruption on dendritic spine density and glutamate receptor composition and function have been reported, 7,13,15,16 as well as effects on long-term potentiation 5,7,17 and long-term depression. 5,7,[13][14][15] Effects of ASIC1A disruption on dendritic spine density and glutamate receptor composition and function have been reported, 7,13,15,16 as well as effects on long-term potentiation 5,7,17 and long-term depression.…”
mentioning
confidence: 99%
“…ASIC1A has been localized to dendritic spines, and implicated in synaptic plasticity and neurotransmission mediated by protons released from neurotransmitter containing vesicles. 5,7,[13][14][15] Effects of ASIC1A disruption on dendritic spine density and glutamate receptor composition and function have been reported, 7,13,15,16 as well as effects on long-term potentiation 5,7,17 and long-term depression. 12 Thus, through its location and function, ASIC1A may be well positioned to influence Pavlovian conditioning.…”
mentioning
confidence: 99%
“…For example, studies of ASIC1a knockout mice showed that these animals exhibit reduced depression and anxiety related behavior [54], reduced fear behavior [55,56], and increased addiction related behavior [49]. Additionally, ASIC1a knockout mice display impaired performance in several learning paradigms, including hippocampal-dependent spatial learning and cerebellar-dependent eyeblink conditioning [57], amygdala-dependent impaired cue and contextual fear conditioning paradigms [51,[58][59][60][61], and impaired extinction of conditioned taste avoidance [53]. Similarly, mutations in the C. elegans ASIC-1 gene cause abnormal performance in an associative learning paradigm [62].…”
Section: Roles Of Deg/enacs In Behaviormentioning
confidence: 99%